2005
DOI: 10.1021/tx0497954
|View full text |Cite
|
Sign up to set email alerts
|

Structural AlertsA New Classification Model to Discriminate Excess Toxicity from Narcotic Effect Levels of Organic Compounds in the Acute Daphnid Assay

Abstract: Quantitative and qualitative structure-activity relationships (QSARs) have a great potential to support the risk assessment of chemicals, provided there are tools available that allow evaluation of the suitability of QSARs for the compounds of interest. In this context, a pragmatic approach is to discriminate excess toxicity from narcotic effect levels, because the latter can be estimated from QSARs and thus have a low priority for experimental testing. To develop a respective scheme for the acute daphnid toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(137 citation statements)
references
References 21 publications
4
133
0
Order By: Relevance
“…Often, individual authors have reported the numerical value as a median immobilization effective concentration at the time of measurement, and in a later paper, the same authors referred to the same measured value as the median lethal molar concentration, and vice versa. Von der Ohe et al (2005) made similar observations regarding the published toxicity data for water fleas in their statement ".... some studies use mortality (LC 50 ) and immobilization (EC 50 , effective concentration 50%) as identical endpoints in the context of daphnid toxicity". Von der Ohe et al made no attempt to distinguish between the two.…”
Section: Abraham Model: Prediction Of Environmental Toxicity Of Pharmmentioning
confidence: 62%
“…Often, individual authors have reported the numerical value as a median immobilization effective concentration at the time of measurement, and in a later paper, the same authors referred to the same measured value as the median lethal molar concentration, and vice versa. Von der Ohe et al (2005) made similar observations regarding the published toxicity data for water fleas in their statement ".... some studies use mortality (LC 50 ) and immobilization (EC 50 , effective concentration 50%) as identical endpoints in the context of daphnid toxicity". Von der Ohe et al made no attempt to distinguish between the two.…”
Section: Abraham Model: Prediction Of Environmental Toxicity Of Pharmmentioning
confidence: 62%
“…Basic toxicity (defined as minimal toxicity correlated with hydrophobicity) of the 65 compounds to the three aquatic organisms were calculated through log K ow regression models (van Leeuwen et al 1992;von der Ohe et al 2005;Ellison et al 2008). The baseline toxicity models for each organism are summarized in Table 2; hydrophobicity, log K ow , was obtained using EPI Suite 4.1 software.…”
Section: Basic and Excess Toxicitymentioning
confidence: 99%
“…Toxicity enhancement (T e ), previously termed excess toxicity, is widely used to determine whether a compound can elicit reactive toxicity through a comparison with its baseline toxicity (von der Ohe et al 2005;Schramm et al 2011). T e ¼ 10 has been proposed as a threshold to discriminate reactive from non-reactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it seems that in the first phase of REACH more pragmatic approaches based on the occurrence of fragments, like in AS-TER or as proposed by von der Ohe et at. [58], will be used with the known limitations described above.…”
Section: Classificationmentioning
confidence: 99%